Schefflera hoi (Dunn) Viguier (Araliaceae)-a Tree New to India - Naithani, H. B.; Bennet, S. S. R. (Indian Forester, 1982)
Schefflera hoi (Dunn) Viguler, a tree native of China, is reported here for the first time from Arunachal Pradesh In India.